Seabirds of the Chukotka Peninsula, Russia - Konyukhov, Nikolai B.; Bogoslovskaya, Ludmila S.V.; Zvonov, Boris M.; Van Pelt, Thomas I. (ARCTIC, 1998)
We conducted seabird surveys along the entire coast of the Chukotka Peninsula (northwestern Siberia, Russia) from 1983 to 1991. We present the first comprehensive descriptions of the distribution and size of Chukotkan seabird colonies. Thirteen species of seabirds were recorded breeding on the peninsula, with an additional 13 migrant or vagrant species. Our estimate that at least 3 300 000 seabirds breed on the Chukotka Peninsula demonstrates the importance of this region to arctic seabird populations. Colony size and species composition may be determined by availability of adequate breeding sites, access to foraging areas, and variable ice conditions. De 1983 à 1991, on a effectué des relevés d'oiseaux marins tout le long du rivage de la péninsule de Tchoukotka (nord-ouest de la Sibérie, en Russie). On présente les premières descriptions exhaustives de la distribution et de la taille des colonies d'oiseaux marins de la Tchoukotka. On a relevé 13 espèces d'oiseaux marins nichant sur la péninsule, et, en plus, 13 espèces d'oiseaux en migration ou errants. Notre estimation d'une population nicheuse d'au moins 3 300 000 oiseaux marins dans la péninsule de Tchoukotka illustre l'importance de la région pour les populations d'oiseaux marins de l'Arctique. La taille des colonies et la composition des espèces pourraient être déterminées par la disponibilité de sites adéquats pour les nids, l'accès à des zones d'alimentation, et la variabilité des conditions de la glace.